2008
DOI: 10.1017/s1355617708080521
|View full text |Cite
|
Sign up to set email alerts
|

Potential for misclassification of mild cognitive impairment: A study of memory scores on the Wechsler Memory Scale-III in healthy older adults

Abstract: The psychometric criterion of mild cognitive impairment (MCI) generally involves having an unusually low score on memory testing (i.e., 21.5 SDs). However, healthy older adults can obtain low scores, particularly when multiple memory measures are administered. In turn, there is a substantial risk of psychometrically misclassifying MCI in healthy older adults. This study examined the base rates of low memory scores in older adults (55-87 years; n 5 550) from the Wechsler Memory Scale-Third Edition (WMS-III; Wec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
146
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(161 citation statements)
references
References 62 publications
14
146
1
Order By: Relevance
“…Second, there is no consensus regarding which neuropsychological tests are most effective in identifying MCI. By using a cut off of ≤ 1.5 standard deviation units we attempted to guard against a type 1 error; however, by permitting a low score on any of six tests, we acknowledge the possibility of making a type 2 error (Brooks, Iverson, & White, 2007 ;Brooks, Grant, Holdnack, & Feldman, 2008 ). Indeed, our rates of discrimination are slightly lower than base rates of low memory performance in older community dwelling adults (Brooks et al, 2007 ), but slightly higher than those reported in large-scale epidemiological studies of pathological aging in patients followed through a memory disorders clinic (Edwards, Lindquist, & Yaffe, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is no consensus regarding which neuropsychological tests are most effective in identifying MCI. By using a cut off of ≤ 1.5 standard deviation units we attempted to guard against a type 1 error; however, by permitting a low score on any of six tests, we acknowledge the possibility of making a type 2 error (Brooks, Iverson, & White, 2007 ;Brooks, Grant, Holdnack, & Feldman, 2008 ). Indeed, our rates of discrimination are slightly lower than base rates of low memory performance in older community dwelling adults (Brooks et al, 2007 ), but slightly higher than those reported in large-scale epidemiological studies of pathological aging in patients followed through a memory disorders clinic (Edwards, Lindquist, & Yaffe, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…The domains assessed were Memory (CVLT-II, WMS-III Logical Memory, WMS-R Verbal Paired Associates, WMS-R Visual Paired Associates, WMS-III Faces, and Rey Figure Recall), Language (Phonemic Fluency, Semantic Fluency, Boston Naming Test), Visual-Spatial (WASI Block Design, Rey Figure Copy), and Executive (Trail Making Test Part B, Wisconsin Card Sorting Task). Requiring two or more tests within a domain to be impaired within a domain reduces the likelihood of false positive identification of MCI [18]. Based on this test battery, four individuals had single-domain amnestic MCI, two had single-domain non-amnestic MCI, and four had multi-domain amnestic MCI.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Because healthy older adults may obtain some low memory scores [18] there is substantial concern regarding false-positive diagnosis of memory impairment [19][20][21][22][23] . If memory impairment is misdiagnosed [see ref.…”
Section: Introductionmentioning
confidence: 99%